Investigating the Contribution of Different Types of Red Meat Consumption on Air Pollution in Iran - Hamid Reza Izadi; Mojtaba Mohammadnejadi; Niloofar Sarani (International Journal of Management, Accounting and Economics)
Since the production and consumption of meat are known to be among the leading causes of greenhouse gas emissions and environmental pollution, this study examines the relationship between the consumption of various types of red meat by households and its impact on air pollution and environmental contamination in Iran. For this purpose, this article tests this relationship using annual time series data from 1980 to 2019 and the FMOLS method. The findings indicate that the consumption of red meat has a negative effect on environmental pollution because it leads to air pollution and increases environmental pollution. According to the results, the consumption of cow and veal meat has a greater contribution on air pollution and environmental pollution, and the consumption of camel meat has the lowest contribution. Furthermore, the growth of consumption, which leads to the development of production in the economy, can result in air and environmental pollution, as meat production is an energy and input-intensive process. In light of these findings, policymakers must focus on controlling household consumption and production of these products by implementing tax and incentive policies to decrease environmental pollution